Relation between Feed Particle Size Distribution and Plumage Condition in Laying Hens on Commercial Farms - Ruben Schreiter; Klaus Damme; Markus Freick (Animals, 2021)
In this cross-sectional study, 103 complete feed samples from laying hen herds affected by plumage damage as an indirect measure for severe feather pecking (affected herds; AH, n = 37) and control herds without plumage damage (control herd; CH, n = 66) of commercial German farms were examined by dry sieve and nutrient analysis. AH showed higher percentages of particles >2.50 mm (mean ± SD, CH: 11.0 ± 8.5%, AH: 24.9 ± 14.3%) and 2.00–2.50 mm (CH: 11.2 ± 5.3%, AH: 15.7 ± 5.7%), but lower proportions of fractions 1.01–1.60 mm (CH: 22.9 ± 4.9%, AH: 17.8 ± 5.7%), 0.51–1.00 mm (CH: 25.5 ± 8.2%, AH: 16.0 ± 6.8%) and ≤0.50 mm (CH: 15.4 ± 5.0%, AH: 11.0 ± 4.8%) (p < 0.001). Diets of AH had a higher geometric mean diameter (GMD) compared to CH (AH: 1470.8 ± 343.9 μm; CH: 1113.3 ± 225.7 μm) (p < 0.001). Contents of crude ash (CH: 130.3 ± 18.8 g/kg, AH: 115.9 ± 24.3 g/kg), lysine (CH: 8.2 ± 1.0 g/kg, AH: 7.7 ± 1.2 g/kg), methionine (CH: 3.4 ± 0.5 g/kg, AH: 3.2 ± 0.6 g/kg) and sodium (CH: 1.7 ± 0.4 g/kg, AH: 1.3 ± 0.4 g/kg) were lower in AH (p ≤ 0.041). In a logistic regression model, animal age (p = 0.041) and GMD (p < 0.001) were significant factors on the occurrence of plumage damage.